Novel waterproof ambient cured geopolymer concrete using integral crystalline waterproofing admixture (Advances in Civil and Architectural Engineering, 2025)
Geopolymer concrete (GC) is a promising alternative to conventional cement concrete owing to its environmental benefits. However, water penetration, which is a common concern, significantly affects the performance of GC, thus causing efflorescence, reinforcement corrosion, and scaling, among other durability issues, which affect its longevity. The present study attempts to clarify the efficacy of incorporating an integral crystalline waterproofing admixture in enhancing the durability of GC by reducing the penetration of water into the concrete matrix. The samples are subjected to compressive-strength and split-tensile-strength tests to evaluate the material’s strength properties. Additionally, water absorption, chloride penetrability, water contact angle, and acid-resistance tests are performed to ascertain the durability of the modified GC. The results show that GC samples with a 3 % crystalline waterproofing content performs the best, i.e., it reduced water absorption by 42,85 %, 40,90 %, and 45,26 % after 7; 28; and 56 days of curing. In addition to improving water absorption, the admixture significantly enhances the mechanical strength of GC, with increases in compressive strength by 15,74 %, 15,65 %, and 15,86 % at 7, 28, and 56 days, respectively. Additionally, scanning electron microscopy analysis is performed on the GC samples to understand the changes in the microstructure of GC mixes with various dosages of the crystalline waterproofing agent added to them.